(untitled) (Gaceta Técnica, 2018)
The Construction Camera of the Lara State in Venezuela has been encouraging courses through the agreement established with the School of Civil Engineering of the Centroccidental University Lisandro Alvarado, with the purpose of updating and maintaining a system of continuous training of its members in the construction area. It has specialized chairs taught at higher levels within the civil engineering career itself, as is the subject "Construction Management" to specific courses in the structural area. Likewise, the Internship Unit is supported by locating students who need to complete professional internships in companies affiliated with the Camera; including consultancies in degree works from the civil engineering area